Reconstruction of destroyed cities. 1943-2023 - Bush, Dmitry (project baikal, 2023)
The Russian Academy of Architecture and Construction Sciences continues to develop a new tradition of organising large exhibitions on the theme of the Academy’s general meetings. The exhibition on the theme “Reconstruction of Destroyed Cities” aims to compare the practices of urban reconstruction in the USSR, Japan, Western and Eastern Europe and in contemporary Russia. The exhibition covers cities that have been destroyed in military operations as well as those that have suffered from earthquakes. The presentation boards focus on the cities of Stalingrad, Smolensk, Sevastopol, Ashgabat, Tashkent, Grozny, Mariupol, Coventry, London, Magdeburg, Hiroshima, Nagasaki, Tokyo, Bremen, Warsaw, Berlin, Leipzig, Gdansk, Skopje, Hanover, Kassel, Kiel and Lubeck.
Keywords: RAACS General Assembly 2023; exhibition “Reconstruction of Destroyed Cities”